Answer:
(f · g)(t - 1) = 4t² - 2t - 13
Explanation:
First, find (f · g)(n). You can do this by multiplying f(n) by g(n).
f(n) = 2n - 2
g(n) = 2n + 5
(f · g)(n) = (2n - 2)(2n + 5)
(f · g)(n) = 4n² + 6n - 10
Now, plug (t - 1) into (f · g)(n) and simplify.
(f · g)(n) = 4n² + 6n - 10
(f · g)(t - 1) = 4(t - 1)² + 6(t - 1) - 10
(f · g)(t - 1) = 4(t² - 2t + 1) + 6(t - 1) - 10
(f · g)(t - 1) = 4t² - 8t + 4 + 6t - 1 - 10
(f · g)(t - 1) = 4t² - 8t + 4 + 6t - 1 - 10
(f · g)(t - 1) = 4t² - 2t + 4 - 1 - 10
(f · g)(t - 1) = 4t² - 2t - 13